Expression analysis of liver-specific circulating microRNAs in HCV-induced hepatocellular Carcinoma in Egyptian patients. Issue 5 (4th May 2018) - Mourad, Lobna; El-Ahwany, Eman; Zoheiry, Mona; Abu-Taleb, Hoda; Hassan, Marwa; Ouf, Amged; Rahim, Ali Abdel; Hassanien, Moataz; Zada, Suher
ABSTRACT: Objectives : Due to the absence of reliable and accurate biomarkers for the early detection of liver malignancy, circulating microRNAs have recently emerged as great candidates for prompt cancer identification. Therefore, the aim of this study was to investigate the potential of liver-specific circulating microRNAs as an accurate non-invasive diagnostic tool for early diagnosis of hepatitis C virus (HCV)-induced hepatocellular carcinoma (HCC). Methodology : A total of 165 patients were enrolled in this study and categorized into four main groups: 42 chronic hepatitis C (CHC) without cirrhosis, 45 CHC with cirrhosis (LC), 38 HCC with HCV patients, and 40 healthy controls. The expression profiles of seven miRNAs (miR-16, miR-34a, miR-125a, miR-139, miR-145, miR-199a, and miR-221) were analyzed using real-time PCR. Results : Serum levels of miRNA-125a, miRNA-139, miRNA-145, and miRNA199a were significantly lower ( p < 0.01) in HCC than in both CHC and LC groups. On the other hand, no significant difference was shown in the expression of miR-16, miR-34a, and miR-221 between the CHC, LC, and HCC groups. MiR-16, miR-34a, and miR-221 were significantly elevated in the HCC group compared to the control group. MiR-34a showed the highest specificity and sensitivity. Conclusions : The results indicated that the measurement of serum levels of miR-125a, miR-139, miR-145, and miR-199a can help to differentiate HCC from CHC and LC. Also, miR-16, miR-34a, and miR-221 serum levels would have a prognostic value. MiR-34a had the highest specificity and sensitivity, indicating that it might serve as a novel and potential non-invasive biomarker for HCV-induced HCC.